A conceptual framework for the work–life balance of police officers: a post-COVID-19 perspective - Sandhya D. S. (Cogent Business & Management, 2024)
This study has undertaken a comprehensive review of literature from 2019 to 2021, encompassing work/life balance review articles to identify the research gap in the work/life balance area. Employing the PRISMA framework for systematic literature review, the study identified prospective areas for future research on work/life balance and variables associated with work/life balance in the police sector. The articles published between 2013 and 2023 relating to the police force over the past decade were reviewed to frame a conceptual framework for the work/life balance of police officers. Further literature review attests that there is a research gap in the police sector. The primary goal is to identify the area (work/life balance in the police sector) that lacked research and establish a conceptual framework addressing the work/life balance of police officers, even in challenging situations like COVID-19. The articles related to police from 2013 to 2023 were scrutinised through the PRISMA framework to identify variables necessary for constructing the conceptual framework for police officers. This article, set in the post-COVID-19 era, delves into the factors influencing police officers' capacity to uphold a healthy work–life balance. By pinpointing those research gaps, the article proposes a conceptual framework designed to help police officers balance their professional and personal lives. Such a framework can aid organisations in formulating effective strategies for employee well-being, facilitating work–life balance even in challenging circumstances, such as those imposed by the COVID-19 pandemic.Investigating work/life balance within the police force holds substantial advantages for the community and law enforcement organisations. Foremost, a police force that maintains equilibrium and mental well-being is better equipped to safeguard and serve the public. This research aims to pave the way for formulating policies and methodologies that strengthen the welfare of officers, resulting in heightened levels of public safety. When officers have ample time for rest and personal life, they are more inclined to make rational decisions, exhibit sound judgment, and respond effectively to challenges like the COVID-19 pandemic. Delving into this area of research sheds light on the intricate challenges police officers face as they strive to harmonize their personal and professional lives, pinpointing areas necessitating additional support and resources. By addressing these hurdles, police departments can cultivate a more favourable work environment, ultimately benefiting the community.
Keywords: 650; Work/life balance; police officers; social support; resilience; job satisfaction